ANALYSIS OF FACTORS CONTRIBUTING TO WORK STRESS AMONG EXPATRIATE AIRLINES CREW IN SAUDI ARABIA - Molina, Prima; Teresa; V.V Satvika, Maharani; E. Gunawan, Fergyanto (Universitas Islam Balitar, 2024)
Work stress can significantly impact the performance of cabin crew in the airline industry, potentially leading to job errors with critical implications for safety, a paramount concern in the industry. The research focuses on factors influencing work stress among cabin crew, providing a valuable reference for improving both service quality and safety in the industry. The potential key factors that affect work stress, including workload, cross-cultural adjustment, rotating work schedules, interpersonal relationships, organizational relationships, and physical demands, are established through extensive literature reviews. The relevant data were collected from a sample of cabin crews in Saudi Arabia representing various nationalities. The most pertinent factors for the problem setting are determined by applying a multivariate regression analysis, where the theoretical understanding is statistically verified. The analysis suggests that the theory is supported by the sample data with a fitness level of 0.85 in terms of the determination coefficient, implying strong materialization of the theory. Furthermore, the agreement between theory and reality is supported by the ANOVA and t-tests. The study concludes that workload is the most dominant factor affecting work stress, followed by organizational relationships and rotating work schedules. Statistically less significant factors include cross-cultural adjustment, interpersonal relationships, and physical demands.